The Correlation of Length of Work and Mental Workload with Work Stress at University Lecturers - Kenia Bella Christy1 , Noeroel Widajati1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The main role of lecturers at Tri Dharma University, namely education, research, and community service. That makes them have certain responsibilities which if it lasts a long time will cause stress. This study aims to determine the correlation between work time and mental workload with work stress on college lecturers in Surabaya. This descriptive study was conducted on 43 active lecturers who teach at a university in Surabaya. The results of this study were analyzed to determine the lecturer’s length of work, the mental workload of lecturers with categories from NASA TLX and their correlation with work stress. The results stated that 22 people had worked for more than 20 years, as many as 25 people had very high mental workloads, and 30 people with mild stress. Most of the lecturers already have a lot of experience and a large number of task demands but are still able to deal with everything well so that work stress does not arise. The correlation value between the length of work and work stress is 0.461, and the correlation value between mental workload and work stress is 0.808. This value states there is no correlation between the length of work and mental workload with work stress. Recommendations are given to universities, lecturers and all those involved in efforts to maintain the atmosphere and work culture to improve comfort for all parties, such as adding green areas in the workspace, providing remuneration for lecturers who excel, and maintaining communication between lecturers.